2013
DOI: 10.1016/j.actpsy.2013.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Working memory capacity and dual-task interference in picture naming

Abstract: Researchers have found no agreement on whether dual-task interference in language performance, such as dual-task interference from tone discrimination on picture naming, reflects passive queuing or active scheduling of processes for each task. According to a passive-queuing account, while a central response-selection bottleneck is occupied by the tone discrimination task, picture naming is held in a passive queue until the bottleneck is freed. In contrast, according to an active-scheduling account, participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
62
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(78 citation statements)
references
References 65 publications
10
62
4
Order By: Relevance
“…Thus, Schnur and Martin obtained additive effects of SOA and stimulus type, compatible with Figure 1B. Furthermore, Piai and Roelofs (2013) also failed to replicate the underadditivity of stimulus type and SOA effects using the SOAs Figure 1. Schematic illustration of a lexical response-selection bottleneck account of the stimulus onset asynchrony (SOA) effect on semantic interference in dual-task performance.…”
mentioning
confidence: 64%
See 4 more Smart Citations
“…Thus, Schnur and Martin obtained additive effects of SOA and stimulus type, compatible with Figure 1B. Furthermore, Piai and Roelofs (2013) also failed to replicate the underadditivity of stimulus type and SOA effects using the SOAs Figure 1. Schematic illustration of a lexical response-selection bottleneck account of the stimulus onset asynchrony (SOA) effect on semantic interference in dual-task performance.…”
mentioning
confidence: 64%
“…Stimulus type and paradigm interacted, F 1 (2, 30) ϭ 7.46, p ϭ .002, indicating that the interference effects for the Stroop paradigm were larger than the Stroop-like effects in PWI. Importantly, the Stroop-like effects for the PWI task were significant, incongruent vs. congruent, t 1 (15) ϭ 5.50, p Ͻ .001, 95% confidence interval (CI) [55,128] Schnur and Martin (2012) and Piai and Roelofs (2013) observed for the semantic interference effect, but it differs from what Ayora et al (2011), Dell'Acqua et al (2007, and van Maanen et al (2012, Experiment 1) observed. The additivity of the effects of stimulus type and SOA suggests that the effects occurred at the response-selection stage or later (see Figure 1B), in disagreement with the proposal of a pre-selection locus by Dell'Acqua et al Moreover, given that all written words were phonologically regular, the findings do not agree with the account of Kleinman (2013).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations